INTEGRATING MANUAL MICROSCOPIC REVIEW WITH AUTOMATED CELL COUNTING TO ENHANCE DIAGNOSTIC SENSITIVITY AND SPECIFICITY IN HEMATOLOGY (The Research of Medical Science Review, 2025)
This study investigated the combination of manual microscopic blood smear analysis with automated cell counting to enhance the diagnostic sensitivity and specificity in hematology. Despite progress in automated systems, manual techniques remain crucial for comprehensive blood cell morphology analysis; however, they are susceptible to observer variability and time limitations. This study aimed to assess whether integrating manual and automated methods improves diagnostic precision in identifying hematologic abnormalities. A comparative examination of 500 blood samples was conducted at University of Veterinary and Animal Sciences, Lahore, Pakistan, with each sample manually assessed using an automatic hematological analyzer. Statistical analyses, such as Chi-Square, Cohen's kappa, and paired t-tests, were used to evaluate the sensitivity, specificity, diagnostic duration, and concordance between the two methodologies. The findings indicated that the integrated method achieved a sensitivity of 81.43% and a specificity of 92.00%, outperforming each technique. Furthermore, no substantial variation in diagnostic duration was observed between the manual and automated techniques. The Cohen's kappa coefficient demonstrated moderate concordance between the manual and automated systems. These findings suggest that a combination of manual and automated techniques can improve diagnostic efficacy, offering both speed and precision. This study emphasizes the potential of this integrated strategy to enhance clinical workflows and diagnostic accuracy in hematology, offering a pragmatic alternative to address the shortcomings of each method when used in isolation. Future studies should investigate larger sample sizes and evaluate the cost-effectiveness of integrating diagnostic tools into clinical practice.